Ticagrelor monotherapy after PCI in patients with concomitant diabetes mellitus and chronic kidney disease: TWILIGHT DM-CKD. Issue 7 (23rd March 2022) - Dehghani, Payam; Cao, Davide; Baber, Usman; Nicolas, Johny; Sartori, Samantha; Pivato, Carlo A; Zhang, Zhongjie; Dangas, George; Angiolillo, Dominick J; Briguori, Carlo; Cohen, David J; Collier, Timothy; et al.
Abstract: Aims: We aimed to evaluate the treatment effects of ticagrelor monotherapy in the very high risk cohort of patients with concomitant diabetes mellitus (DM) and chronic kidney disease (CKD) undergoing percutaneous coronary intervention (PCI). Methods and results: In the TWILIGHT (Ticagrelor with Aspirin or Alone in High-Risk Patients after Coronary Intervention) trial, after 3-month dual antiplatelet therapy with ticagrelor and aspirin post-PCI, event-free patients were randomized to either aspirin or placebo in addition to ticagrelor for 12 months. Those with available information on DM and CKD status were included in this subanalysis and were stratified by the presence or absence of either condition: 3391 (54.1%) had neither DM nor CKD (DM−/CKD−), 1822 (29.0%) had DM only (DM+/CKD−), 561 (8.9%) had CKD only (DM−/CKD+), and 8.0% had both DM and CKD (DM+/CKD+). The incidence of the primary endpoint of Bleeding Academic Research Consortium (BARC) type 2, 3, or 5 bleeding did not differ according to DM/CKD status ( P -trend = 0.13), but there was a significant increase in BARC 3 or 5 bleeding ( P -trend < 0.001) as well as the key secondary endpoint of death, myocardial infarction, or stroke ( P -trend < 0.001). Ticagrelor plus placebo reduced bleeding events compared with ticagrelor plus aspirin across all four groups, including DM+/CKD+ patients with respect to BARC 2–5 [4.5% vs. 8.7%; hazard ratio (HR) 0.49, 95% confidence interval (CI) 0.24–1.01] as well as BARC 3–5 (0.8% vs. 5.3%; HR 0.15, 95% CI 0.03–0.53) bleeding, with no evidence of heterogeneity. The risk of death, myocardial infarction, or stroke was similar between treatment arms across all groups. Conclusion: Irrespective of the presence of DM, CKD, and their combination, ticagrelor monotherapy reduced the risk of bleeding without a significant increase in ischaemic events compared with ticagrelor plus aspirin.